1979
DOI: 10.1159/000181652
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Peritoneal Dialysis, Haemodialysis and Kidney Transplantation on Blood Platelet Function

Abstract: Quantitation of the thrombocytopathy of uraemics may be one useful way of evaluating forms of therapy. 24 patients treated by haemodialysis and peritoneal dialysis at two different times had platelet aggregation studies whose parameters were compared with those of 24 normal persons, 5 successful transplants or 13 untreated uraemics. Renal transplantation and peritoneal dialysis improved platelet function. The haemodialysis procedure itself impaired platelet function: this was not due to heparin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(20 citation statements)
references
References 16 publications
2
18
0
Order By: Relevance
“…Bemiset al [19] reported findings similar to that of us, but others have described in vitro platelet aggregation as being either normal [14,15] or reduced [16][17][18] in HD patients. This has been explained on the basis that HD plasma contains certain platelet inhibitory substances [14] as well as increased levels of prostacyclin (PG12) [23].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Bemiset al [19] reported findings similar to that of us, but others have described in vitro platelet aggregation as being either normal [14,15] or reduced [16][17][18] in HD patients. This has been explained on the basis that HD plasma contains certain platelet inhibitory substances [14] as well as increased levels of prostacyclin (PG12) [23].…”
Section: Discussionsupporting
confidence: 66%
“…In vivo studies have demonstrated enhanced platelet activity in this population [1][2][3][4][5][11][12][13], Conflicting data, however, have been reported regarding in vitro platelet aggregation which was found to be normal [14,15], re duced [16][17][18], and increased [19] in chronic HD patients in comparison to nonuremic controls. Our study was undertaken to reevaluate in vitro platelet aggregation in CRF subjects treated by HD.…”
Section: Introductionmentioning
confidence: 99%
“…The persistence of this abnormality in the chronically dia- lyzed patients may be a reflection on the intermittency of the uremic environment, between dialyses. Alternatively, the hemodialysis procedure itself has been implicated to impair platelet function [7] and may have been responsi ble for the persistent abnormality. The lower values for membrane ATPase in the transplant recipients are more difficult to attribute to uremia.…”
Section: Discussionmentioning
confidence: 99%
“…defective platelet reten tion on glass beads [1,5], abnormal platelet aggregation [2] and poor clot retraction [2,6]. That this is a reversible phe nomenon and a consequence of the abnormal biochemical uremic environment has been documented by the observa tion that platelet function returns to normal following dial ysis or renal transplantation [6,7], Other than a brief com munication of a defect in platelet serotonin uptake and storage in uremia [8], the biochemistry of platelets in renal failure has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…• Correct the hematocrit to >0AE30 [60,61] • Consider the use of desmopressin [34,62,63] • Consider the use of dialysis, which also have haemostatic benefits in this situation [64,65] • Only use platelet transfusions where the above methods are inappropriate or ineffective [34]. In drug-induced platelet dysfunction such as use of aspirin, NSAIDs or anti-platelet drugs, the following recommendations should be followed.…”
Section: Platelet Transfusionsmentioning
confidence: 99%